MARY PEPCHINSKI, MARIANN SIMON (eds.) - Ideological Equals: Women Architects in Socialist Europe 1945-1989 - Menlioğlu, Ayşe Hilal (ZARCH, 2022)
Mary Pepchinski, Mariann Simon (eds.) Ideological Equals: Women Architects in Socialist Europe 1945-1989 Abingdon, New York: Routledge, 2017. 195 pp. Tapa dura. Idioma: inglés. 52 € ISBN-10: ‏ 1472469267 ISBN-13: 978-1472469267